2016
DOI: 10.1177/0284185116656492
|View full text |Cite
|
Sign up to set email alerts
|

Predicting tumor recurrence in patients with cervical carcinoma treated with definitive chemoradiotherapy: value of quantitative histogram analysis on diffusion-weighted MR images

Abstract: Background Further research is required for evaluating the use of ADC histogram analysis in more advanced stages of cervical cancer treated with definitive chemoradiotherapy (CRT). Purpose To investigate the utility of apparent diffusion coefficient (ADC) histogram derived from diffusion-weighted magnetic resonance images in cervical cancer patients treated with definitive CRT. Material and Methods The clinical and radiological data of 50 patients with histologically proven cervical squamous cell carcinoma tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 26 publications
1
21
1
Order By: Relevance
“…To date, there have been a few studies assessing the utility of radiomics analysis of ADC in cervical cancer. Although these studies have been performed using a volumetric approach, they used different b values and different methods of region of interest (ROI) positioning; that is, ROI covered all voxels including cystic or necrotic areas within the tumor on all slices, or ROI contained solid components of tumor while avoiding hemorrhagic, necrotic, or cystic regions . Undoubtedly, volumetric tumor ADC delineation could provide a more comprehensive evaluation of underlying spatial heterogeneity; however, it is typically not widely available in routine clinical practice and is still time‐consuming .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there have been a few studies assessing the utility of radiomics analysis of ADC in cervical cancer. Although these studies have been performed using a volumetric approach, they used different b values and different methods of region of interest (ROI) positioning; that is, ROI covered all voxels including cystic or necrotic areas within the tumor on all slices, or ROI contained solid components of tumor while avoiding hemorrhagic, necrotic, or cystic regions . Undoubtedly, volumetric tumor ADC delineation could provide a more comprehensive evaluation of underlying spatial heterogeneity; however, it is typically not widely available in routine clinical practice and is still time‐consuming .…”
mentioning
confidence: 99%
“…15,16 Successful applications of this technique have been performed on oncologic DWI datasets. 15,17,18 To date, there have been a few studies [19][20][21][22][23][24][25] assessing the utility of radiomics analysis of ADC in cervical cancer. Although these studies have been performed using a volumetric approach, they used different b values and different methods of region of interest (ROI) positioning; that is, ROI covered all voxels including cystic or necrotic areas within the tumor on all slices, 23,24 or ROI contained solid components of tumor while avoiding hemorrhagic, necrotic, or cystic regions.…”
mentioning
confidence: 99%
“…With this method, a volumetric ROI is positioned on the entire lesion over contiguous slices, and a histogram of ADC values reflecting the frequency of voxels is constructed. The approach of whole‐lesion histogram analysis eliminates the subjectivity inherent in the placement of a focal ROI, leading to better evaluation of heterogeneity …”
mentioning
confidence: 99%
“…The approach of whole-lesion histogram analysis eliminates the subjectivity inherent in the placement of a focal ROI, leading to better evaluation of heterogeneity. [20][21][22][23] Recently, as personalized and targeted approaches to therapies are being pursued in the field of oncology, accurate tumor characterization is essential for selecting appropriate treatment. Diffusion-weighted imaging (DWI) can reflect the tissue microstructure, and emerging evidence suggests that quantitative ADC assessment may help to differentiate tumor subtypes.…”
mentioning
confidence: 99%
“…Dynamic MRI permits evaluation of tumor response to chemoradiotherapy by analysis of tumor hypoxia and tumor interstitial pressure 21. Apparent diffusion coefficient has been identified as a good biomarker and modifications of its value during chemoradiotherapy have been associated with treatment response and survival 22. A prospective cohort study in which 92 women underwent PET examination 3 months after the end of the treatment found that residual tumor was significantly associated with decreased progression free survival 23.…”
Section: Discussionmentioning
confidence: 99%